Africa within the world : beyond dispossession and dependence - Adedeji, Adebayo; African Centre for Development and Strategic Studies (London : Zed Books, 1993)
In this book, leading figures, both African and non- African, explore ways and means of revitalising the continent's economic, social and political foundations. The plea for a strategic reorientation towards universal value and common global survival, within and outside Africa, emerges as a thread throughout: the right and need to (re)claim and creatively draw upon Africa's history and culture; to hold accountable national and international leaders; and to seek collective, sustainable and equitable solutions from the local to the global level-- (Back Cover)
The book was first published by Zed books Ltd, London UK and Atlantic Highlands, New Jersey USA in association with the African Centre for development and strategic studies., Ijebu - Ode, Nigeria.
Includes Index
rpm 30/08/16
Loans
Keywords: Africa; Foreign relations -- 1960-; Diplomatic relations; Politics and government -- 1960-; Economic conditions -- 1960-; Economic integration; Economic policy; Social policy; Africa